2014
DOI: 10.1074/jbc.m114.563650
|View full text |Cite
|
Sign up to set email alerts
|

The Epigenetic Drug 5-Azacytidine Interferes with Cholesterol and Lipid Metabolism

Abstract: Background:The anticancer drug 5-azacytidine acts through an incompletely understood mechanism. Results: 5-Azacytidine reprograms the glycerolipid biosynthesis pathway and prevents activation of master transcription factors that regulate lipid homeostasis. Conclusion: 5-Azacytidine deeply modifies how cells manage cholesterol and lipid synthesis. Significance: The findings unravel important insights into the mechanism of 5-azacytidine and highlight new potential cancer therapeutics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 55 publications
1
29
0
Order By: Relevance
“…These two generations were also shorter, but as yet there is no link established between hypomethylation and body length. However, it should be noted that 5-azacytidine and other nucleoside analogues are not specific DNA methylation inhibitors and also affect other pathways (Gnyszka et al, 2013;Poirier et al, 2014).…”
Section: Epigenetics In Life Phase Transitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…These two generations were also shorter, but as yet there is no link established between hypomethylation and body length. However, it should be noted that 5-azacytidine and other nucleoside analogues are not specific DNA methylation inhibitors and also affect other pathways (Gnyszka et al, 2013;Poirier et al, 2014).…”
Section: Epigenetics In Life Phase Transitionsmentioning
confidence: 99%
“…These two generations were also shorter, but as yet there is no link established between hypomethylation and body length. However, it should be noted that 5-azacytidine and other nucleoside analogues are not specific DNA methylation inhibitors and also affect other pathways (Gnyszka et al, 2013;Poirier et al, 2014).Further evidence for epigenetic inheritance in Drosophila and Daphnia is reviewed elsewhere (Youngson and Whitelaw, 2008), but the mechanisms of this 'soft' inheritance are generally not well understood.Evidence for epigenetics in locusts DNA methylationTo our knowledge, the earliest study on DNA methylation in locusts dates from 1951 (Wyatt, 1951), and reported that 0.96% of all cytosines are methylated in L. migratoria. Surprisingly, these early findings were followed by a 60 year gap.…”
mentioning
confidence: 99%
“…Among the genes found to be elevated in Slfn2 eka/eka in comparison to wild‐type monocytes are: ACAT2 , which codes for the ER membrane‐bound sterol O ‐acyltransferase 2, which produces intracellular cholesteryl esters from long‐chain fatty acyl CoA and cholesterol; AGPAT9 (1‐acylglycerol‐3‐phosphate O ‐acyltransferase 9, the gene encoding for GPAT3), which regulates triacylglycerol biosynthesis and cytosolic lipid droplet formation; meteorin‐like ( METRNL ), which is highly expressed in activated monocytes and during adipogenesis and encodes for a protein that promotes lipid metabolism and inhibits adipose inflammation . Furthermore, our gene profile analysis showed that Slfn2 eka/eka monocytes have highly reduced levels of the genes ALOX15 , FABP4 and HPGD , which have regulatory roles in fatty acid and cholesterol metabolism, fatty acid uptake/transport and lipid/prostaglandin metabolism, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It eradicated the berberine effect on HNF1α and PCSK9 gene transcription process [55]. A diminished expression of PCSK9 and of other key genes involved in cholesterol and lipid metabolism was obtained in vitro and in vivo (in mouse liver) using 5-azacytidine, a DNA-hypomethylating agent [56], utilized in the treatment of myelodysplastic syndrome and acute myeloid leukemia. This drug inhibits de novo pyrimidine synthesis, followed by a disruption of lipid and cholesterol metabolism [56].…”
Section: Other Drugs That Influence Pcsk9 Metabolismmentioning
confidence: 99%